2005
DOI: 10.1108/09540910510613510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SnAgCu composition on soldering performance

Abstract: PurposeTombstoning and voiding have been plaguing the surface mount assembly industry for decades. The recent global move toward lead‐free soldering and the extensive adoption of microvia technology further aggravate the problems. The present study investigates the impact of SnAgCu (SAC) alloy composition on these important issues.Design/methodology/approachIn this study, tombstoning and voiding at microvias are studied for a series of SAC lead‐free solders, with an attempt to identify a possible “composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
0
10
1
Order By: Relevance
“…Comparing the results with the other investigators' studies [9,10,23], it is found that there are some discrepancies between our results and their findings. Huang et al [9] found that solder joints with ENIG finishes on PCB revealed longer lifetime than those with OSP finishes.…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…Comparing the results with the other investigators' studies [9,10,23], it is found that there are some discrepancies between our results and their findings. Huang et al [9] found that solder joints with ENIG finishes on PCB revealed longer lifetime than those with OSP finishes.…”
Section: Discussioncontrasting
confidence: 79%
“…Huang et al [9] found that solder joints with ENIG finishes on PCB revealed longer lifetime than those with OSP finishes. The predominant failure mode was the tearing of PCB trace in the OSP samples.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations